PERBANDINGAN KREDIT PEMILIKAN RUMAH PADA BANK KONVENSIONAL DENGAN PEMBIAYAAN KEPEMILIKAN RUMAH PADA BANK SYARIAH - PUSPITA SARI, PUTRI Puspita (Jurnal Akuntansi AKUNESA, 2013)
Inthisstudydiscusses thedifferencesbetweenthe provisionofmortgagesonconventionalbankfinancingof home ownershipinIslamic banks. Theresultsofthis studyindicate adifference inthe systems used inconventionalbankstoIslamicbanks. The most fundamental differenceis thesystem ofinterestareusedinconventionalbankingandlosssharingprincipleinIslamic banking. Withthesystem of interestrateissetto changeat any timein accordancewithbankpolicies, whereas ifyouuse theprinciple ofprofit sharingandlossmargincan not bechangedbecause itis inconformitywith themurabahacontract.Keywords:mortgageloans, conventionalbank,Islamic banks.